DETERMINING THE RIGHT DOSAGE OF INORGANIC FERTILIZERS TO INCREASE GROWTH AND RESULTS THREE LOCAL UPLAND RICE CULTIVARS - Usman Made; Mustakim Mustakim (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Fertilization is one of the important factor to increase production. The aim of this study was to determine the appropriate dosage of inorganic fertilizers to increase the growth and yield of three cultivars of upland rice. This research was conducted at the Center for Research and Development of Gogo Rice, Faculty of Agriculture, Tadulako University, Kalama, Tamarenja Village at an altitude of 180 to 250 above sea level with a latitude of 00o 26'51.5” South Latitude and 119o49'50.6” East Latitude, Sindue District, Donggala Regency, Central Sulawesi Province. The time of the research started from March to August 2020. This research was compiled and carried out using the factorial 2 factors Randomized Block Design (RBD) method. The first factor used three local upland rice cultivars, namely: Pae Bohe, Buncaili, and Uva Buya, while the second factor used six doses of inorganic fertilizers, namely: No fertilization, NPK fertilization 100 kg/ha, 200 kg/ha, 300 kg/ha, 400 kg/ha, and 500 kg/ha. There were 18 combinations, where each treatment was repeated three times so that there were 54 research units. Parameters observed included plant height, number of productive tillers, age of panicle appear, harvest age, number of panicle grains, percentage of empty grain, 1000 grain weight and production. The results showed that the Pae bohe cultivar with fertilization dose of 500 kg/ha produced the highest number of productive tillers (6.69 per clump), the lower percentage of grain pests (5.34%), and the highest production (3.82 tons/ha).